The Influence of the oval, lane and simultaneous entry on the performance and pacing strategy of speed skating men's 1500 m - Feng, J.; Zhou, Y.; Min, L.; Li, X. (Journal of Science in Sport and Exercise, 2021)
Objective: To explore the influence of the oval (plateau or plain), the lane (inner or outer), and simultaneous entry (long distance or sprint) on the result and pacing strategy in speed skating men`s 1500 m. Methods: Multi-factor analysis of variance, independent sample T test, Spearman correlation coefficient method, paired T test and other statistical methods are used to analyze the relationship and differences between the oval (plateau or plain), the lane (inner or outer), and/or simultaneous entry (long distance or sprint) and the results of the top 8 athletes of the ISU event in the 2019-2020 season. Results: Among the three factors of oval, lane, and simultaneous entry, only the altitude will improve the athlete`s performance of 1500 m, an increase of about 2.52% (2.65 s). Both the oval and the simultaneous entry will affect the athlete`s 1500 m pacing strategy. Athletes tend to adopt a more positive strategy when competing in plateau; the sprint athletes have a faster opening, but a slower ending. Conclusion: At present, the level of speed skating in China and the world is in the highest period. Among the oval factors, the highland oval can significantly improve the athletes` performance of 1500 m; athletes tend to adopt a more positive pacing strategy in the plateau than in the plain. In the process of preparing for the 2022 Winter Olympic Games, we can predict the competitive level of the opponent through the plateau competition results and carry out targeted preparation. Different lanes do not affect the athlete`s 1500 m performance and pacing strategy but may affect the athlete`s final lap speed. There is no obvious difference between the sprint and long-distance athletes on the performance of 1500 m, but the sprint athletes have a faster opening and a slower ending, and the long-distance athletes have a faster final lap and a smaller drop between each lap.